Effect of food supply on foraging patterns and body weights of long-toed stints (Calidris Subminuta) - Somchai Nimnuan (2018)
Multiple species of shorebirds are now globally threatened, particularly across tropical Asia, yet we know relatively little of the detailed habitat usage and resource characteristics of sites in the region. The objective of this study was to determine how seasonal variation in food density affected foraging patterns and body weights of Long-toed Stint (Calidris subminuta), a relatively common winter visitor. Research was conducted during the passage and overwintering seasons in wastewater treatment ponds and salt-pans on the Inner Gulf of Thailand. Predictions were that during periods of higher food density, shorebirds should be relatively more abundant and heavier, and have increased foraging attempts, reduced step rates and reduced chase rates. Furthermore, adults were expected to have higher weights than juveniles. Overall, shorebird abundance was significantly positively correlated with invertebrate abundance during the 2-year study period. Long-toed Stints had greater body mass following their arrival in July-September, compared with later periods during the winter. Although food density and Long-toed Stint step rate were not significantly correlated, the data were consistent with previous studies suggesting a negative relationship. Step rates in salt-pans were significantly higher than in the wastewater treatment ponds, probably reflecting lower food densities in the salt-pans. There was no clear relationship between food density and Long-toed Stint peck rate, perhaps reflecting the weak correlation between number of pecks and the number of successful foraging bouts as well as limited sample sizes for prey estimates. There was no significant relationship between food density and chase rates. There was no significant difference in median body mass between adults and juveniles/first-year birds, implying young birds learn to forage as efficiently as adults relatively rapidly. This study suggests that further work on invertebrate dynamics and shorebird diets in the region is needed in order to build more predictive models of shorebird site usage and population dynamics.